2022
DOI: 10.1371/journal.pone.0278235
|View full text |Cite
|
Sign up to set email alerts
|

Psychological distress among people living with chronic medical illness and the general population, Northwest Ethiopia: A comparative cross-sectional study

Abstract: Background Psychological distress is often linked to and negatively affects the outcomes of chronic medical conditions; however, data on psychological distress and its predictors among individuals with chronic medical illnesses are scarce in developing countries like Ethiopia. The main objective of this study was to assess the magnitude and predictors of psychological distress among people living with chronic medical illness and the general population. Methods A comparative cross-sectional study was conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…However, lower prevalence were reported in Ethiopia (22.8%) ( 61 ), and India (33.2%) ( 62 ). A similar study conducted in Bangladesh found a low prevalence of anxiety (35.2%) and depression (38.9%) ( 60 ). On the other hand, higher prevalence were also reported in studies conducted in Harar (62%) ( 60 ), and Mettu Karl Referral Hospital 55.7% (depression) and 61.8% (anxiety) ( 59 ).…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…However, lower prevalence were reported in Ethiopia (22.8%) ( 61 ), and India (33.2%) ( 62 ). A similar study conducted in Bangladesh found a low prevalence of anxiety (35.2%) and depression (38.9%) ( 60 ). On the other hand, higher prevalence were also reported in studies conducted in Harar (62%) ( 60 ), and Mettu Karl Referral Hospital 55.7% (depression) and 61.8% (anxiety) ( 59 ).…”
Section: Discussionmentioning
confidence: 86%
“…A similar study conducted in Bangladesh found a low prevalence of anxiety (35.2%) and depression (38.9%) ( 60 ). On the other hand, higher prevalence were also reported in studies conducted in Harar (62%) ( 60 ), and Mettu Karl Referral Hospital 55.7% (depression) and 61.8% (anxiety) ( 59 ). Moreover, other pre-COVID-19 researches indicated higher estimates of mental health problems in different parts of the world such as 63.3% in Ethiopia ( 63 ), 60.2% in Pakistan ( 64 ), 64.4% in Nigeria ( 65 ), and (58.7%) in Delhi, India ( 66 ).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…As for somatopsychic disorders, the mechanism is thought to be immune-mediated, though little is still understood (22,23). This knowledge gap necessitates further studies to be conducted as the list of somatopsychic disorders continues to expand with our scientific understanding (7,24).…”
Section: Introductionmentioning
confidence: 99%